Estudio de factibilidad para la puesta en marcha de una iniciativa empresarial dedicada a la prestación del servicio de aseo doméstico en la ciudad de Armenia (2014)
The domestic cleaning service is an unfulfilled necessity in the higher social classes of Armenia city, since there is no enterprise dedicated to the provision of such service, and it is increasing the widespread fear of informally hiring housekeepers due to the existence of high standards, laws and sanctions involving large sums of money to pay for the service, including social benefits, social security and wages. This study has an important social component owing to the involvement of staff with special conditions such as mothers’ head of household with low education which are promised a wage, social security and benefits just like the law demands. Through this investigation made by means of surveys, it has been determined the size of the target market, we can see then, the acceptation of the service that is supposed to be offered, the level of expected sales, the indirect competition, the general conditions of the personnel, the client’s requirements, among other aspects. Besides, make an analysis of facility’s size, important organizational and financial aspects that show indicators and financial statements demonstrating the feasibility of the project, budget higher than the initial investment, internal return rate greater than the rate of opportunity, and expected profits from the first year of operation of the business.